Why Randomize Agricultural Experiments?. Issue 5 (2nd April 2013) - Piepho, H. P.; Möhring, J.; Williams, E. R.
Abstract This study illustrates the importance of randomization using two hypothetical field trials, one with a marked systematic trend and the other with a more erratic spatial pattern. The insights from these two examples are reinforced by analysis of a uniformity trial and a small simulation study. Results illustrate that both model‐based spatial analysis and randomization‐based analysis assuming independent errors are valid with full randomization but may be invalidated when randomization is lacking. It is concluded that randomization provides protection against different forms of spatial trend. The examples given in the study serve as a general reminder that agricultural experiments should be randomized whenever possible.